1971
DOI: 10.1111/j.1365-2052.1971.tb01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of canine serum albumin

Abstract: Three serum albumin phenotypes were observed in a population of 257 dogs consisting of 18 breeds and breed crosses. Canine serum albumins are controlled by an auto-soma1 locus with two codominant alleles AlbF and Albs. Separation of the albumin types was possible by using buffer solutions with a pH of about 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…comm.) 1969DAY eta1 1971DAY et al 1971NIELSEN 1969NIELSEN 1969KOMMA 1968FILDES and HARRIS 1966ASHTON and BRADEN 1961o r KOMMA 1968YNDGARD 1972BAUR and SCHORR 1969SIMONSEN and FRYDENBFRG 1972SHAW and PRASAD 1970 March 29, 1973). Table 3 lists the proteins studied (with abbreviations).…”
Section: Wasmund 1966mentioning
confidence: 99%
See 1 more Smart Citation
“…comm.) 1969DAY eta1 1971DAY et al 1971NIELSEN 1969NIELSEN 1969KOMMA 1968FILDES and HARRIS 1966ASHTON and BRADEN 1961o r KOMMA 1968YNDGARD 1972BAUR and SCHORR 1969SIMONSEN and FRYDENBFRG 1972SHAW and PRASAD 1970 March 29, 1973). Table 3 lists the proteins studied (with abbreviations).…”
Section: Wasmund 1966mentioning
confidence: 99%
“…They found a significant difference in the gene BAUME 1962;LAWRENCE 1966;FIENNES and FIENNES 1968;HERRE and R~H R S 1973) they are still closely related to the other Canidae. For instance, the domestic dog and the coyote (Cunis lafrans) have the same 78 chromosomes (Mammalian Chromosomes I , folio 20 and 21, 1967), and while the jackal BWND and AUSTAD 1973DAY et al 1971SEARCY et al 1966BYVOET and GOTTI 1967FUNAKOSI and DEUTSCH 1971ALLISON et al 1957FERNSTEIN et al I968 WONC et al 1972AUGUSTINSSON 1961NAIK et al 1971KAMADA and HORI 1970FLEISHER et al 1960NAIK et al 1971NAIK et al 1971TANABE et al 1974NAIK et al 1971HANLEY et al 1966 (HERRE 1971;HERRE and ROHRS 1973). Dog-wolf hybrids are also fertile.…”
mentioning
confidence: 99%
“…Polymorphism of transferrin (Tf) (STEVENS and TOWNS-LEY 1970), eserine resistant esterase (Es) (SUGIURA et al 1977). and leucine aminopeptidase (Lap) (TANABE et al 1974) was reported by alkaline starch gel electrophoresis while that of albumin (Al) (DAY et al 1971) was studied by acid starch gel electrophoresis. In two recent studies on alkaline polyacrylamide gel electrophoresis of dog plasma proteins, genetic polymorphism of two post-albumins (Pa-I and Pa-3) (REETZ et al 1980) and improved separation of transferrins (JLINEJA et al 1981a) was reported.…”
mentioning
confidence: 99%